Antimicrobial activity of bacteriocins of lactic acid bacteria on Listeria monocytogenes, Staphylococcus aureus and Clostridium tyrobutyricum in cheese production - Dolenčić Špehar, Iva; Bendelja Ljoljić, Darija; Petanjek, Zvjezdana; Zamberlin, Šimun; Tudor Kalit, Milna; Samaržija, Dubravka (2020)
The generally accepted concept of the necessity of producing safe foods has indirectly influenced the decision to replace chemical preservatives with natural ones. Bacteriocins, and in particular those synthesized by lactic acid bacteria (LAB) in the food industry, are considered to be their effective replacement. In controlling the growth of microbial pathogens and/or the occurrence of pathogenic bacteria in food, with the permitted nisin and pediocin, a significant antibacterial effect has been shown for most LAB bacteriocins. However, the use of purified bacteriocins as bio preservatives in cheese production is limited. To inhibit the growth of bacteria L. monocytogenes, S. aureus and C. tyrobutyricum in cheese, bacteriocinogenic LAB strains contained in primary, adjunct or protective culture are much more acceptable in cheese production.
Opće prihvaćen koncept o nužnosti proizvodnje zdrave i sigurne hrane neizravno je utjecao na odluku da se i kemijski konzervansi zamijene prirodnim. Bakteriocini, a osobito oni koje sintetiziraju bakterije mliječne kiseline (BMK) u prehrambenoj se industriji smatraju njihovom učinkovitim zamjenom. U kontroli rasta mikrobnih uzročnika kvarenja i/ili pojavnosti patogenih bakterija u hrani, uz dopušteni nizin i pediocin i za većinu je do sada opisanih i pročišćenih bakteriocina BMK utvrđen značajan antibakterijski učinak. Međutim, primjena pročišćenih bakteriocina kao biokonzervansa u proizvodnji sira je limitirana. Za inhibiciju rasta bakterija L. monocytogenes, S. aureus i C. tyrobutyricum u siru, znatno su prihvatljiviji bakteriocinogeni sojevi BMK sadržani u primarnoj, dopunskoj ili protektivnoj kulturi od pročišćenih bakteriocina.
Bibliografija: 107 jed.
Summary ; Sažetak.
Keywords: Sir -- Bakterije mliječne kiseline -- Listeria monocytogenes -- Staphylococcus aureus -- Clostridium tyrobutyricum